Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1165/rcmb.2003-0097oc
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Neuroepithelial Bodies and Their Innervation in Fawn-Hooded and Wistar Rat Lungs

Abstract: The Fawn-Hooded rat (FHR), a model for primary pulmonary hypertension, shows an unexplained hypersensitivity to airway hypoxia. Because pulmonary neuroepithelial bodies (NEBs) appear to express a functional oxygen-sensing mechanism and an extensive sensory innervation, possible changes in this system should be taken into consideration. In the present study a comparative analysis of NEBs and their selective innervation was performed in FHRs and Wistar control rats. In both rat strains, the number of NEBs was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…This suggested a role for purinergic regulation of NEBs during intrauterine life, when the density of NEBs was high, suggesting that NEBs may act as chemoreceptors for hypoxia before the carotid body chemoreceptors, which are known to be relatively immature at birth (Brouns et al, 2003a). This group later showed that approximately 40% of NEBs were innervated by vagal sensory fibers, approximately 50% by calcitonin gene-related peptide-immunoreactive DRG sensory fibers, and approximately 10% by intrinsic pulmonary nitrergic nerves (Van Genechten et al, 2004). Another research group demonstrated that both P2X2 and P2X3 receptor immunoreactivity on hamster NEBs was identified with 5-hydroxytryptamine (5-HT), a marker for NEBs (Fu et al, 2004).…”
Section: Lung and Intrapulmonary Airwaysmentioning
confidence: 99%
“…This suggested a role for purinergic regulation of NEBs during intrauterine life, when the density of NEBs was high, suggesting that NEBs may act as chemoreceptors for hypoxia before the carotid body chemoreceptors, which are known to be relatively immature at birth (Brouns et al, 2003a). This group later showed that approximately 40% of NEBs were innervated by vagal sensory fibers, approximately 50% by calcitonin gene-related peptide-immunoreactive DRG sensory fibers, and approximately 10% by intrinsic pulmonary nitrergic nerves (Van Genechten et al, 2004). Another research group demonstrated that both P2X2 and P2X3 receptor immunoreactivity on hamster NEBs was identified with 5-hydroxytryptamine (5-HT), a marker for NEBs (Fu et al, 2004).…”
Section: Lung and Intrapulmonary Airwaysmentioning
confidence: 99%
“…These vagal sensory nerve Wbers were shown to be myelinated and capsaicin insensitive, and express vesicular glutamate transporter (VGLUT) 1 and 2 (VGLUTs are transmembrane proteins that load glutamate into synaptic vesicles), the calcium-binding protein calbindin D-28 k (CB), and P2X 3 ATP receptors or Na + /K + -ATPase 3 (Brouns et al 2000(Brouns et al , 2006a. Apart from the vagal innervation, neurons in thoracic dorsal root ganglia (DRG) (Springall et al 1987, own unpublished observations) appear to give rise to an unmyelinated capsaicinsensitive C-Wber-like calcitonin gene-related peptide (CGRP)-and substance P (SP)-immunoreactive (-ir) nerve Wber population that does not penetrate the epithelium, but rather forms a nervous plexus at the basal pole of rat NEBs (Cadieux et al 1986;Shimosegawa and Said 1991;Adriaensen et al 2003;Brouns et al 2003;Van Genechten et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary NEBs in rats were further shown to be selectively contacted by intraepithelial neuronal nitric oxide synthase (nNOS)-ir (nitrergic) nerve Wbers, which originate from intrinsic nitrergic airway neurons that co-localize vasoactive intestinal polypeptide (VIP) and are invariably surrounded by CGRP-ir C-Wber terminals (Brouns et al 2002a, b;Adriaensen et al 2003;Van Genechten et al 2004). Finally, vesicular acetylcholine transporter (VAChT)-ir cholinergic nerve terminals were reported in direct contact with rat NEBs (Pintelon et al 2003;Van Genechten et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurosecretory or neuroendocrine cells (Kultschitzky cells) are present individually or in very small clusters within the epithelium at all levels of the respiratory tract (Edmondson and Lewis, 1980;Dormans, 1983;Genechten et al, 2004;Adriaensen et al, 2003). Neurosecretory cells are identified ultrastructurally by characteristic electrondense secretory cytoplasmic granules that contain serotonin, calcitonin, bombesin, and encephalin (Adriaensen et al, 2003).…”
Section: Trachea Bronchi and Bronchiolesmentioning
confidence: 99%